Anticipating Patient Anxiety Through Spiritual Education at Dr. Drs. M. Hatta Brain Hospital Bukittinggi - Zain, Najmal Hadi; Zakir, Supratman; Hanani, Silfia; Sesmiarni, Zulfani; Rozi, Syafwan (International Journal Labs, 2025)
The purpose of this study was to explore spiritual education as a way to anticipate patient anxiety. This study applies a mixed-methods approach, namely combining quantitative and qualitative methods. In the quantitative section, the HARS (Hamilton Anxiety Rating Scale) instrument was used to measure the level of anxiety of respondents objectively before and after the intervention. Meanwhile, the qualitative approach was carried out through in-depth interviews to explore the experiences and perceptions of participants regarding the intervention given. The results of the quantitative study showed that spiritual education can anticipate patient anxiety. It was found that the level of anxiety in the pre-test for most patients was at a moderate level, with 73.33%, whereas the level of anxiety in the post-test for most patients was at a mild level, with 66.77%. Qualitative results support this finding, with participants reporting increased inner peace, a sense of sincerity, and decreased fear when hospitalized. Spiritual education can handle anxiety through material on monotheism, dhikr therapy, and prayer, which are very effective when applied in hospitals to reduce the anxiety of hospitalized patients.